Improvement for alignment process of automotive assembly plant using simulation and design of experiments. (1st January 2011) - Altayib, Khaled; Ali, Ahad
This paper develops and discusses a discrete event simulation model for alignment process of automotive assembly plant. It also includes optimisation, design of experiments and meta-modelling studies. This simulation assists to understand the current process performance and capacity, key processes or procedures impacting throughput and production efficiency. The model modified to reflect changes aimed at optimising the process performance and layout, to increase efficiency, improve throughput and reduce cost.